Educação física na área das linguagens - Souza, Dainan Lanes de (2018)
This study aims to analyze the implications of semiotic structuring in the process of legitimacy of Physical Education in relation to the area of languages, justified by the need for recognition of professionals involved in the relationship established in this area of knowledge in basic education. The methodology is characterized by a theoretical study, of a dialectical method, with a refined bibliographical revision, where the teaching documents of Physical Education in the area of languages (National Curricular Parameters [PCN's, 1999] and the National Curricular Common Base [BNCC, 2017]) and the works constituted during the period of approval of these documents. The results indicate that there is no homogeneity in the concept of language presented in the guiding documents, and the need to construct a grammar for body language, which can be established by the Motory Praxiology (PM), through an analytical concept of Semiotics which can be the starting point for a pedagogical intervention through a propositional concept of Semiotics given by the Pedagogy of Corporeity (PC). These are aspects of communication and language relevant in the teaching process learning the manifestations of the body culture of movement that can corroborate in the recognition of this component in this area of knowledge.